Teacher–Student Relationships in Special Education: The Value of the Teacher Relationship Interview. (October 2019) - Koenen, Anne-Katrien; Vervoort, Eleonora; Verschueren, Karine; Spilt, Jantine L.
Research on teacher–student relationships is mainly based on questionnaires investigating teachers' explicit cognitions. However, it is also important to investigate implicit processes in social interactions, such as internalized feelings. The Teacher Relationship Interview (TRI) is a narrative method aimed at assessing teachers' (implicit) mental representations of dyadic teacher–student relationships. The TRI may provide—for researchers as well as practitioners—a deeper understanding of teachers' implicit cognitive and emotional processes elicited in teacher–student relationships, which can be useful for psychodiagnostic assessment and relationship-focused consultation with teachers. This study investigated the psychometric properties of the TRI in a special education sample of students with symptoms of attachment disorders ( N = 80). Expected interrelations of the TRI scales were found with a widely used questionnaire of teacher–student relationships, independent observations of teacher–student interactions, and teacher perceptions of student behavior.